Software Composition 8th International Conference, SC 2009, Zurich, Switzerland, July 2-3, 2009. Proceedings - Bergel, Alexandre; Fabry, Johan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the 8th International Symposium on Software Composition, SC 2009, held in Zurich, Switzerland, in July 2009. The workshop has been organized as an event co-located with the TOOLS Europe 2009 conference. The 10 revised full papers presented together with 2 invited lectures were carefully reviewed and selected from 34 submissions. The papers reflect current research in software composition to foster developing of composition models and techniques by using aspect- and service-oriented programming, specification of component contracts and protocols, methods of correct components composition, as well as verification, validation and testing techniques - even in pervasive computing environments and for the Web.
Language Design for Meta-programming in the Software Composition Domain -- Putting Traits in Perspective -- Feature (De)composition in Functional Programming -- I-Java: An Extension of Java with Incomplete Objects and Object Composition -- Language-Independent Quantification and Weaving for Feature Composition -- Lazy Composition of Representations in Java -- Specifying and Composing Non-functional Requirements in Model-Based Development -- Round-Trip Support for Invasive Software Composition Systems -- Implicit First Class Genericity -- A Framework for Testing Model Composition Engines -- Composing RESTful Services with JOpera -- Writing Composable Software with InterpreterLib.
Keywords: Computer science; Computer communication systems; Software engineering; Computer programming; Programming languages (Electronic computers).; Computer logic; Computer Science; Software Engineering/Programming and Operating Systems; Software Engineering; Programming Techniques; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Computer Communication Networks; Electronic books